Case report of heterotaxy syndrome with sinus node dysfunction and left ventricular hypertrabeculation: clinical and genetic insights - Matta, María Gabriela (2025)
We present the case of a 41-year-old woman with left atrial isomerism, severe sinus node dysfunction, and left ventricular hypertrabeculation, who required implantation of a dual-chamber implantable cardioverter-defibrillator with left bundle branch area pacing. Her family history revealed multiple cases of heterotaxy and conduction disorders. Genetic testing identified a heterozygous interstitial duplication on chromosome 17q23.2 involving the MED13 gene, whose clinical significance has not yet been determined.